Spontaneous rupture of extraluminal jejunal gastrointestinal stromal tumor causing acute abdomen and hemoperitoneum - (:unkn) unknown (AVES, 2015)
Tumor perforation is accepted as an important prognostic factor along with tumor size and mitotic index in gastrointestinal stromal tumors (GIST). The prognosis is worse in patients with tumor perforation or rupture. A few case reports of small bowel GIST presenting with rupture have been published in the medical literature. We report an unusual case of a 7.5 cm GIST of the jejunum that presented with spontaneous rupture. A previously healthy 46-year-old male patient presented with sudden abdominal pain. Physical examination revealed overt peritonitis, and computed tomography showed a heterogeneous solid mass measuring approximately 6 cm x 5.5 cm arising from the jejunum and massive fluid in the peritoneum. The mass was diagnosed as a GIST originating from the gastrointestinal tract. Emergency laparotomy was performed and intraoperative findings showed massive hemoperitoneum and an outgrowing mass at the jejunum, 50 cm distal to the Treitz ligament. The tumor had ruptured near the wall of the small intestine and it was actively bleeding. Surgical resection of the tumor was performed and the patient was discharged home uneventfully on the third postoperative day. The immunohistochemical characteristics of the tumor revealed it to be a GIST.
Keywords: Gastrointestinal stromal tumor; rupture; acute abdomen; hemoperitoneum; DIAGNOSIS; RESECTION